Offenders' perceptions of the UK prison smoking ban. Issue 2 (10th June 2019) - Dugdale, Stephanie; Semper, Heather; Povey, Rachel; Elison-Davies, Sarah; Davies, Glyn; Ward, Jonathan
Abstract : Purpose: Despite overall reductions in levels of smoking in the UK, rates of offender smoking remain high. In 2016, it was announced that prisons in England and Wales would gradually introduce a smoking ban. The purpose of this paper is to explore offenders' perceptions around the upcoming smoking ban. Design/methodology/approach: A total of eight focus groups were conducted in four prisons across the North of England. Both smoking and non-smoking offenders participated in the focus groups, and thematic analysis was used to explore the findings. Findings: Themes generated from the data were "freedom and rights", "the prison environment" and "guiding support". Participants discussed how the smoking ban was viewed as a punishment and restricted their freedom, with perceptions as to why the ban was being implemented centring around others trying to control them. Participants expressed concerns around the financial implications of the smoking ban on already stretched prison resources. Participants also recommended improving the nicotine replacement therapy on offer, and increasing the range of leisure activities within the prison to prepare for the smoking ban. Originality/value: Overall, it was apparent that participants' awareness of the smoking ban was generally poor. It is recommended that offenders need to be made more aware of the smoking cessation support they will receive and given the opportunity to ask questions about the smoking ban. Increasing offenders' awareness of the ban may reduce stress associated with a perceived lack of choice around their smoking behaviours.